Mitigating the impacts of river flow regulation and barriers to fish spawning migrations - Baker, Nicola Joanne (2018)
Globally, migratory fish are threatened by anthropogenic modification to rivers. These create barriers that prevent fish accessing spawning grounds required for completion of life cycles. In order to make informed decsions, for mitigating the associated negative impacts, an understanding migratory behaviour when reaching barriers during the spawning migration is required. That said, there is a lack of information about the response of migratory fish to operational regimes in regulated rivers and the areas occupied, delays caused and routes taken around infrastructures. This study investigated the behaviour of three migratory fish species under operational regimes of three different infrastructures during each species’ respective spawning season. The efficiency of a bypass channel that utilised the relationship between migratory behaviour and flow was also investigated for a further species. The literature was reviewed to identify the different types of migratory life histories of fish, the impact of different riverine modification on the respective spawning migrations and how this can be mitigated. Fish have evolved in direct response to the natural flow regime and connectivity of riverine habitats, but barriers to migration exist from source to sea. This regulates or disrupts the flow regime and connectivity that fish depend upon, which has had considerable detriment to many migratory fish species globally. The main conclusion of the review was that knowledge gaps exist for the target species, and understanding the behaviour of the study species during the spawning migration is essential to improve access to spawning grounds in regulated rivers and ultimately conserve populations. The effects of timing, magnitude and duration of eleven artificial flow (freshet) releases from two impounding reservoirs on river-resident brown trout (Salmo trutta L.), a species known to undertake spawning migrations, was investigated using radio telemetry in a regulated upland river in northern England. Most did not perform movements characteristic of spawning migrations; all were located within 10 m of the location occupied before freshets, and fish in a control reach behaved comparably. The largest unidirectional movements mostly occurred during elevated river level due to rainfall and reservoir overtopping events; other varied length movements occurred during natural peaks or low flow, indicating artificial freshets were not directly responsible, and may not be suitable to stimulate migration in river-resident fish in regulated rivers. An acoustic telemetry study was conducted to determine the impact of a high- head hydropower station, associated diversion weir and spillway on downstream migrating shortfin eel (Anguilla australis) in the regulated Wairua catchment, Northland, New Zealand. Despite the diversion weir providing an alternative route, 88% (n = 21) of tagged eels that were detected here entered the power station forebay; of these, 52% were impinged onto intake screens, always when turbines were operating at greater than 3.04 MW/day. The rest (48%) passed the spillway and continued their migration, sometimes after long delays and having spent time immediately upstream of the intake where fitness could have been reduced due to high flows. Based on findings, the most effective mitigation here and at similar power schemes is considered to be operational or physical changes at the diversion weir to minimise entry of downstream migrating eels into the power canal during the migration period. Also discussed as potential solutions are turbine shutdowns, ensuring the spillway is available and provision of a bypass channel in the forebay. At a pumping station in the Anglian region, UK, where the upstream river level is maintained primarily by a co-located gravity sluice door, route choice and behaviour of downstream migrating European eel (Anguilla anguilla) (n = 7) immediately upstream of both routes was investigated using acoustic telemetry. During the study, three eels passed through pumps despite only operating for 8% of the time the gravity sluice was open, and only two passed through the gravity sluice after arriving when it was closed; the remaining two retreated upstream. No eels were detected within 15 m of the gravity sluice when it was open and eel behaviour was indicative of reluctance to pass through pumps. Findings are discussed in terms of water resource management to implement operational changes, to make the gravity sluice an attractive downstream passage route for migrating eels and thus reduce passage through hazardous pumps. The efficacy of two bypasses in attracting and passing downstream migrating American eels (Anguilla rostrata), designed to utilise the relationship between eel migratory behaviour and flow through two methods of flow creation, i.e. an airlift and a siphon, was tested in a simulated forebay environment, as a potential remediation measure at infrastructures requiring eel passage. Under entrance velocity of 1.2 m/s in eight test runs, both bypasses performed comparably and eels tested in each readily located, entered and passed. Test findings are discussed in relation to real-world application at sites with different characteristics, and the suitability of each design in successfully providing a safe route for downstream migrating eels.
HydraID: hull:18364 Hydra Discover Access Group: public ETD Collection: ETDHullInternationalFisheriesInstitute
Keywords: Fisheries